A prospective examination of the impact of high levels of exercise training on sedentary behaviour. Issue 2 (7th February 2017) - Swartz, Ann M.; Miller, Nora E.; Cho, Young IK; Welch, Whitney A.; Strath, Scott J.
Abstract: The aim of this study is to determine changes in sedentary behaviour in response to extensive aerobic exercise training. Participants included adults who self-selected to run a marathon. Sedentary behaviour, total activity counts and physical activity (PA) intensity were assessed (Actigraph GT3X) for seven consecutive days during seven assessment periods (−3, −2, and −1 month prior to the marathon, within 2 weeks of the marathon, and +1, +2, and +3 months after the marathon). Models were fitted with multiple imputation data using the STATA mi module. Random intercept generalized least squares (GLS) regression models were used to determine change in sedentary behaviour with seven waves of repeated measures. Results : Twenty-three individuals (mean ±  S x : 34.4 ± 2.1 y, 23.0 ± 1.9% fat, 15 women, 8 men) completed the study. Marathon finishing times ranged from 185 to 344 minutes (253.2 ± 9.6 minutes). Total counts in the vertical axis were 1, 729, 414 lower one month after the race, compared with two months prior to the race (peak training). Furthermore, counts per minute decreased by 252.7 counts·minute −1 during that same time period. Daily sedentary behaviour did not change over the seven assessment periods, after accounting for age, gender, per cent body fat, wear time, marathon finishing time, and previous marathon experience. This prospective study supports the notion that PA and sedentary behaviours are distinct, showing that sedentary behaviour was not impacted by high levels of aerobic training.